A Study on motivation comic ‘MISI 10A’ / Nur Aifah Mohad Azami - Mohad Azami, Nur Aifah (2019)
Many parents argue that comics are just entertainment and do not benefit their children or their schooling. But comics have a lot of visuals or cartoons that are very much liked by children who can remember from writing. Comic motivation in education is very effective for readers and can influence the mind to learn. To convey a message to a reader is to require story planning read by readers. The storyline and main character in the comic plays a major role in promoting the child's motivation or inspiration from this comic. The researcher learned to convey motivation to the reader there is a stream of storytelling in which there is a creative storytelling